Scoring efficiency in elite football: a technical-tactical analysis of top scorers in Europe`s top five leagues (2023/2024) - Ivanov, D. (Science, Movement & Health, 2025)
Aim. The 2023/2024 football season in Europe's top five leagues (Premier League, La Liga, Bundesliga, Serie A, and Ligue 1) revealed unique trends in goal scoring and tactical behavior among elite goal scorers. The study's main objective is to investigate the technical-tactical actions of the top scorers.